Investigating knowledge, attitude, and self-care behavior concerning Aedes mosquito bites and the knowledge of dengue fever among Hormozgan residents in the south of Iran - Ali Asadian; Abdoljabbar Zakeri; Masoud Dadras; Sheila Mahdavi (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: In recent years, with the identification of the Aedes mosquito as a vector of dengue fever (DF) in Hormozgan province, this southern province was recognized nationwide at a great risk of DF. The present study was conducted on the Aedes mosquito prevention and DF knowledge in this province. MATERIALS AND METHODS: An online survey was conducted using a self-administered questionnaire for 1 month in 2022. The sampling method was snowball. A total number of 4,004 questionnaires were completed online by the residents of Hormozgan province. Finally, the data were analyzed using descriptive statistics, statistical tests, and statistical software SPSS (Statistical Package for the Social Science) version 22. RESULTS: The level of knowledge, attitude, and behavior concerning the self-care behavior of Aedes mosquito bites was as follows. Most participants were knowledgeable and correctly answered the questions related to the preventive ways of Aedes mosquito bites. The average rate of correct answers was 94.5%. They also mostly held a positive attitude. Regarding the attitude items, most participants (more than 85%) strongly agreed and agreed with the statements. Regarding the behavioral items, most participants (70.4%) stated they showed the aforementioned preventive behaviors to impede Aedes mosquito bites. As for the state of participants' knowledge of how the DF is transmitted, overall, in the nine examined items, on average, 40.6% answered "I do not know" and "false". CONCLUSION: As the education level of the participants showed, they did not know adequately about the DF. Judging the state of knowledge, attitude, and behavior of the less privileged and less educated social classes in Hormozgan province requires further investigation of the public living in this province after some time passes since the implementation of educational and preventive interventions. It is also necessary to enrich population-based educational interventions aiming to improve knowledge and preventive behaviors of the DF and Aedes mosquito.